2013
DOI: 10.1021/ja403577u
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Large Quantum Interference Effect in Anthraquinone Solid-State Junctions

Abstract: Quantum interference in cross-conjugated molecules embedded in solid-state devices was investigated by direct current-voltage and differential conductance transport measurements of anthraquinone (AQ)-based large area planar junctions. A thin film of AQ was grafted covalently on the junction base electrode by diazonium electroreduction, while the counter electrode was directly evaporated on top of the molecular layer. Our technique provides direct evidence of a large quantum interference effect in multiple CMOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 39 publications
5
85
0
1
Order By: Relevance
“…Quantum interference takes place in molecules where the π -electron system is cross-conjugated such as anthraquinone (AQ) and results in a strong suppression of conductance with respect to more conducting linearly conjugated molecules [1][2][3][4][5][6][7]. The resulting suppression of conductance has been reported experimentally using different techniques such as conducting atomic force microscopy [8], eutectic GaIn contact [9], mechanically controllable break junctions [10], and large-area molecular junctions [11]. The AQ molecule, due to its intrinsic cross-conjugated structure, has been used in most of these experimental works under the form of a single molecule and thin films [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum interference takes place in molecules where the π -electron system is cross-conjugated such as anthraquinone (AQ) and results in a strong suppression of conductance with respect to more conducting linearly conjugated molecules [1][2][3][4][5][6][7]. The resulting suppression of conductance has been reported experimentally using different techniques such as conducting atomic force microscopy [8], eutectic GaIn contact [9], mechanically controllable break junctions [10], and large-area molecular junctions [11]. The AQ molecule, due to its intrinsic cross-conjugated structure, has been used in most of these experimental works under the form of a single molecule and thin films [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their small size (on the scale of Angstroms) and the large energy gaps (on the scale of eV), transport through single molecules can remain phase coherent even at room temperature, and constructive or destructive quantum interference (QI) can be utilized to manipulate their room temperature electrical [10][11][12][13] and thermoelectrical 14,15 properties. In previous studies, it was reported theoretically and experimentally that the conductance of a phenyl ring with meta (m) connectivity is lower than the isomer with para (p) connectivity by several orders of magnitude [16][17][18][19][20][21][22][23][24][25] . This arises because partial de Broglie waves traversing different paths through the ring are perfectly out of phase leading to destructive QI in the case of meta coupling, while for para or ortho coupling they are perfectly in phase and exhibit constructive QI.…”
mentioning
confidence: 99%
“…A similar molecule, namely, the anthraquinone was recently shown to exhibit DQI features in the dI/dV. 9,10 The two electronegative oxygen atoms are EW which is reflected by the molecular levels being drawn down in energy. The LUMO is now closer to E F than the HOMO.…”
Section: Re[g Molmentioning
confidence: 99%
“…[4][5][6][7][8] Molecules such as anthraquinone have recently been shown to exhibit destructive QI (DQI) effects in a molecular junction. 9,10 A simple nearestneighbour tight-binding model of the π system has been used to rationalise the QI effects. Moreover, schemes have been developed to make predictions based on simple graphical rules.…”
Section: Introductionmentioning
confidence: 99%